Legal Protection of the Authority for Parate Execution of Fiduciary Collateral for Collection Companies and Financial Services Business Actors - Sonny Alfian Blegoer Laoemoery; Nyoman Satyayudha Dananjaya (Politeknik Siber Cerdika Internasional, 2026)
Background: The dynamic in the implementation fiduciary collateral in Indonesia after Constitutional Court Decisions Number 18/PUU-XVII/2019 and Constitutional Court Decision Number 2/PUU-XIX/2021. The influence of the Constitutional Court ruling has shifted the creditor-centric mechanisms for execution of fiduciary collateral as now it requires debtor consent or a court process. This change, in turn, has important implications for consumer protection in the financial services industry and about the responsibilities of third-party collection companies. Objective: The purpose of this study is to analyze legal protection for financial services (PUJK) business actors and collection companies in connection with the implementation of fiduciary guarantee objects following several Constitutional Court verdicts, particularly POJK 22/2023 specifications. Method: Normative juridical legal research method, with Law No. The study is concerned with fiduciary collateral, the authority of PUJK and collection companies and consumer protection regulations. Results: The results of the research analyze legal developments through POJK 22/2023, which regulates fiduciary collateral execution and/or collection practice to provide a clearer line of guidance on the roles of PUJK and collection companies. Highlighting such initiatives are obligatory warning letters, official cooperation agreements as well as behavioral codes for collection activities. Conclusion: POJK 22/2023 is a step to improve legal certainty for PUJK and collection companies, by balancing the rights of creditors with consumer protection. Path forward will depend on positive regulatory developments to establish principle-based accountability standards for collection companies as well as to, harmonize fiduciary collateral execution mechanisms.